Coronavirus Disease 2019 and the Thyroid - Progress and Perspectives - Inaba, Hidefumi; Aizawa, Toru (Frontiers in Endocrinology, 2021)
SARS-CoV-2 infection (COVID-19) is currently a tremendous global health problem. COVID-19 causes considerable damage to a wide range of vital organs most prominently the respiratory system. Recently, clinical evidence for thyroidal insults during and after COVID-19 has been accumulated. As of today, almost all non-neoplastic thyroid diseases, i.e., Graves’ disease, Hashimoto’s thyroiditis, subacute, painless and postpartum thyroiditis, have all been reported as a complication of COVID-19 and causality by the virus has been strongly implicated in all of them. Similar thyroid problems have been reported in the past with the SARS-CoV outbreak in 2002. In this review, we briefly look back at the reported evidence of alteration in thyroid functionality and thyroid diseases associated with SARS-CoV and then proceed to examine the issue with COVID-19 in detail, which is then followed by an in-depth discussion regarding a pathogenetic link between Coronavirus infection and thyroid disease.